Studi Analisa Kekeringan dengan Metode Standardized Precipitation Index (SPI) dan Palmer Drought Severity Index (PDSI) di DAS Kemuning Kabupaten Sampang - Firdaus, Alfian; Harisuseno, Donny; Suhartanto, Ery (Fakultas Teknik, Universitas Brawijaya, 2021)
Drought is a natural disaster that occurs slowly but harms Sampang Regency people's life sustainability. Consider the negative impact of drought,Â analyze the drought index and its distribution are necessary. This study aims to know drought level using Standardized Precipitation Index (SPI) and Palmer Drought Severity Index (PDSI), then to know their correlation with Southern Oscillation Index (SOI) that can represent El Nino Southern Oscillation (ENSO). Drought index with bigger correlation mapped by Inverse Distance Weighting method to know the distribution. SPI method produced the most severe drought in April 2004 on one month deficit period (-3.651). PDSI method developed the most severe drought in September 2001 (-20.628). Based on the PDSI average analysis results for the 1998-2017 period, it is well-known that drought disasters generally start in July and end in October, while the peak of drought occurs in September. The PDSI method has 60% conformity to the SOI value derived from the graphical visualization of the annual average surplus and deficit index, better than the SPI method that only scores 53%. The visualization of the drought distribution map shows that the Districts of Sampang, Torjun, and Camplong need to become prioritized to mitigate future drought disasters because they have a great potential for drought disasters compared to other districts.